ANALYSIS OF THE RESPONSIVENESS OF RICE HECTARAGE TO COMMERCIAL AGRICULTURE LOAN IN NIGERIA FROM 1966 - 2015 - Okpe, E. A.; Abu, O.; Asogwa, B. C. (Journal of Agripreneurship and Sustainable Development, 2018)
This study examined the responsiveness of rice hectarage to commercial agriculture loan in Nigeria from 1966 to 2015 using time series data. The Augmented-Dickey Fuller test was used to test the stationarity of the individual series. The bounds testing were used as a precursor to the application of Autoregressive Distributed Lags (ARDL) to estimate the short-run and long-run elasticities of rice hectarage response to commercial agriculture loan. The empirical results revealed that effect of commercial agriculture loan on rice hectarage was insignificant and inelastic both in the short run (-0.11) and long run (-0.10), an evidence that rice hectarage was not responsive to commercial agriculture loan both in the short-run and long-run. The study concludes that commercial agriculture loan did not make impact on rice hectarage both in the long run and short run. Therefore, the study recommends that government should review its Land Use Act of 1978 to enable producers have more access to land for rice cultivation. Also, the government should increase the amount of loanable funds to ease the ability of farmers to procure all the necessary inputs and make the fund readily and promptly available.